2021
DOI: 10.1155/2021/4699529
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Inhibits the Progression of Bladder Cancer Cells by Downregulating LncRNA-HEIH Expression

Abstract: Background. Sinomenine has been reported to effectively repress the progression of lung cancer and breast cancer. However, the effects of sinomenine in bladder cancer are not well understood. The purpose of this study was to evaluate the effects of sinomenine in bladder cancer. Methods. The mRNA expression of HEIH in bladder cancer cells was measured by RT-qPCR. T24 and SW780 cells were treated with sinomenine for 24 hours. Cell viability was detected by the MTT assay. Cell migration and invasion were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similar to the mechanism by which sinomenine inhibits cell proliferation, sinomenine and its derivatives can also activate the mitochondrial apoptosis pathway in bladder cancer and hepatocellular carcinoma by downregulating lncRNA-HEIH and miR-29 ( 12 , 20 ). In addition, sinomenine can induce apoptosis of pancreatic cancer cells by inducing G0/G1 cell cycle arrest and apoptosis of malignant glioma and liver cancer cells ( 35 ).…”
Section: Sinomenine Induces Tumor Cell Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the mechanism by which sinomenine inhibits cell proliferation, sinomenine and its derivatives can also activate the mitochondrial apoptosis pathway in bladder cancer and hepatocellular carcinoma by downregulating lncRNA-HEIH and miR-29 ( 12 , 20 ). In addition, sinomenine can induce apoptosis of pancreatic cancer cells by inducing G0/G1 cell cycle arrest and apoptosis of malignant glioma and liver cancer cells ( 35 ).…”
Section: Sinomenine Induces Tumor Cell Apoptosismentioning
confidence: 99%
“…LncRNA-HEIH is carcinogenic in various cancers. Xu et al found that lncRNA-HEIH was upregulated in bladder cancer cell lines (T24,5637, HT-1197, TCCSUP and SW 780) ( 12 ). However, sinomenine can downregulate the expression of lncRNA-HEIH, and knockdown of lncRNA-HEIH reversed the inhibition of proliferation in bladder cancer cells.…”
Section: Sinomenine Inhibits Tumor Cell Proliferationmentioning
confidence: 99%
“…Grape seed proanthocyanidins (GSP) is a general term for a large class of polyphenolic compounds that have antioxidant activity. GSP has various biological activities and has been proven to have good antitumor effects, as well as certain inhibitory effects on cervical cancer (Li et al, 2022a), carcinoma of the urinary bladder (Yang et al, 2021a), lung cancer (Xu et al, 2021a;Mao et al, 2023), colon cancer (Aiello et al, 2019;Zhang et al, 2019), liver cancer (Feng et al, 2019), prostate cancer (Chen and Yu, 2019), among others. In a study on liver cancer cells, GSP was found to trigger ROS production, decrease matrix-metalloproteinases (MMPs), and increase caspase-3 activity in HepG2 cells (Wang et al, 2020), proving that GSPs may induce ROS production and, consequently, lead to MMP reduction and caspase-3 activation.…”
Section: Grape Seedsmentioning
confidence: 99%